The Influence of Augmented Reality (AR) Technology Implementation on Purchase Decisions for Wardah Products: The Mediating Role of Shopping Experience - Alisia Silver Stone; Azwardi; Ana Yanovi; Iisnawati; Zakaria Wahab (International Journal of Economics Accounting and Management, 2026)
The rapid advancement of digital technology has encouraged cosmetic companies to integrate Augmented Reality (AR) into online shopping platforms to create more interactive and personalized consumer experiences. Despite the increasing adoption of AR, empirical evidence regarding the mechanism through which this technology influences purchase decisions remains limited, particularly within Indonesia's cosmetics industry. This study aims to examine the influence of Augmented Reality technology implementation on purchase decisions for Wardah products, with shopping experience serving as a mediating variable. A quantitative research approach was employed by distributing questionnaires to 204 Indonesian consumers who had previously used AR features when purchasing Wardah products online. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings reveal that Augmented Reality technology has a positive and significant effect on both shopping experience and purchase decisions. In addition, shopping experience positively influences purchase decisions and partially mediates the relationship between AR technology and purchase decisions. These results indicate that immersive virtual experiences enhance consumers' trust, engagement, and confidence throughout the purchasing decision-making process. This study extends the application of the Technology Acceptance Model (TAM) by confirming the mediating role of shopping experience in the relationship between AR technology and purchase decisions. Furthermore, the findings provide practical implications for cosmetic companies in developing AR-based digital marketing strategies that enhance customer experiences and encourage purchase decisions